Theoretical and Applied Insights on Pistons Buckling According to DNV Regulation - Fantuzzi, Nicholas; Borgia, Fabio (Journal of Offshore Mechanics and Arctic Engineering, 2019)
Pistons are fundamental structural elements in any engineering practices such as mechanical, civil, aerospace, and offshore engineering. Their strength strongly depends on buckling load, and such information is a major requirement in the design process. Euler’s linear buckling equation is the most common and most used model in design. It is well suited for linear elastic members without geometrical imperfections and nonlinear behavior. Several analytical and experimental investigations of typical hydraulic cylin- ders have been carried out through the years but most of the available standards still use a linear approach with many simplifications. Pistons are slender beams with not-uniform cross section, which need a stronger effort than the classical Euler’s approach. The pres- ent paper aims to discuss limitations of current DNV standards for piston design in off- shore technologies when compared to classical numerical approaches and reference results provided by the existing literature.